Incidencia de las principales enfermedades en el cultivo de tabaco (Nicotiana tabacum) en el Ecuador - Peña Liberio, Jarzara Rafaela (2023)
In Ecuador, tobacco is considered a highly profitable crop for producers, considering that the climatic conditions are suitable for a favorable development of quality leaves. All the information obtained was carried out through the technique of analysis, synthesis and summary, with the only objective of establishing the specific information in correspondence to this project, which has as its theme "Incidence of the main diseases in the tobacco crop (Nicotiana tabacum) in Ecuador. From the above detailed, it was determined that the most frequent diseases that affect the development and potential yield of the crop from the nursery stage to harvest are the following: Blue mold (P. tabaci), pata prieta (P. nicotianae), Frog's eye (C. nicotianae), Fusarium (F. oxysporum) and Tobacco mosaic virus (TMV). Blue mold is caused by the fungus P. tabacina and affects young plants in seedlings, from germination to transplanting, different oily aspects appear on the leaves, they lose flaccidity and the plant dies. The fungus F. oxysporum is an important soil-borne pathogen in tobacco cultivation that can cause extensive damage to susceptible tobacco varieties. The disease pata prieta caused by the soil-borne fungus P. nicotianae causes crop losses when soil inoculum is high; it is characterized by large black spots on the leaves with an oily appearance that gradually dry out from the central area. The fungus C. nicotianae causes the first symptoms on the youngest leaves as small round spots with a light brown center; these spots gradually increase in size and cover the entire leaf; in severe infestations, it causes defoliation, resulting in a reduction in the size and quality of tobacco leaves. Chemical control programs allow reducing the incidence and severity of the main diseases in the tobacco crop. Cultural control allows to avoid the presence of the main diseases in the tobacco crop.